History of the growth of the mobile home industry in Wisconsin - Edwards, James C. (My University, 1968)
The History of the Growth of the Mobil Home Industry in Wisconsin is a seminar as a partial fulfillment of the requirements for a masters degree at Wisconsin State University at LaCrosse. The manufacture of mobile homes in Wisconsin has a short history of just over twenty years. The growth of the industry in the state has been substantial and by all indications the future appears bright. Although, Wisconsin is not among the leading producers in the country, it's production and sales growth have compared favorably with those in other states. State manufactures and dealers have experienced few problems, with the exception of image and organization. These problems, however, are minor and are slowly being remedied. This is the first written history of the mobile home industry in Wisconsin. Some facts about Elmer W. Frey, a major contributor to this paper, have been printed in the Marshfield News-Herald, but they do not include most of the information covered in the succeeding pages.
Keywords: Mobile home industry -- Wisconsin -- History